Diagnosis of functional illness presenting with gait disorder. Issue 2 (February 1988) - Thomson, A P; Sills, J A
Abstract : Nine children presented with disturbances of gait that were not caused by organic disease. They all fulfilled at least four out of eight diagnostic criteria. Diagnosis in all had been delayed while organic causes were excluded. Unnecessary and sometimes potentially harmful procedures were performed or proposed for each child. Identification of such children earlier may avoid morbidity and facilitate management.